Emergence of Hypervirulent Ceftazidime/Avibactam-Resistant Klebsiella pneumoniae Isolates in a Chinese Tertiary Hospital - Li, Dan (Infect Drug Resist, 2020)
INTRODUCTION: Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP) is increasingly reported worldwide, but ceftazidime/avibactam (CAZ/AVI)-resistant hvKP isolates have rarely been observed. We attempted to characterize them in clinical CRKP isolates collected from a university hospital in China from March 2016 to March 2018. METHODS: All isolates were analyzed by antimicrobial susceptibility testing, molecular detection of antibiotic resistance determinants, multilocus sequence typing (MLST), SDS-PAGE, and pulsed-field gel electrophoresis (PFGE). The pLVPK-related genetic loci (rmpA2, terW, iutA, and silS) were screened in all CAZ/AVI-resistant CRKP isolates for the presence of virulence plasmids by PCR. Capsule typing, serum killing assay, Galleria mellonella lethality experiments, and mouse lethality assay were conducted to identify CAZ/AVI-resistant hvKP among isolates that carried all four virulence genes. RESULTS: A total of 232 CRKP isolates were collected. Overall, CAZ/AVI-resistance was found in 8.2% (19/232) CRKP isolates isolated from patients with no history of previous CAZ/AVI-based treatment. Among these, 63.2% (12/19) were metallo-β-lactamase-producing K. pneumoniae (MBL-KP), 52.6% (10/19) were Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-KP), and 26.3% (5/19) produced both MBL and KPC. The presence of carbapenemase promoted a very high increase in CAZ/AVI minimum inhibitory concentration only when ompk35 and ompk36 were absent. Alarmingly, nine isolates had all four virulence genes for the presence of virulence plasmids. All nine isolates were considered to be CAZ/AVI-resistant hvKP according to the G. mellonella infection model and mouse lethality assay, with ST23 being the most common type (55.6%, 5/9). CONCLUSION: The newly emerged hypervirulent CAZ/AVI-resistant KP strain might cause a serious threat to public health, suggesting an urgent need for enhanced clinical awareness and epidemiologic surveillance.